2010
DOI: 10.1071/rdv22n1ab204
|View full text |Cite
|
Sign up to set email alerts
|

204 Fatty Acid Composition of Follicular Fluid From Dairy Cows Fed Tropical Forage-Based Diets Supplemented With Increasing Levels of Soybean Oil

Abstract: Recent studies have shown that dietary supplementation with sources rich in polyunsaturated fatty acids (PUFA) can improve reproductive perfor-mance of lactating dairy cows. However, no studies have reported the fatty acids composition of follicular fluid (FF) from dairy cows fed high-PUFA diets. This study aimed to evaluate the fatty acids composition of FF from dairy cows fed tropical forage-based diets containing different levels of soybean oil (SO). Four multiparous Holstein-Zebu cows in midlactation (90 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Feeding ewes diets high in polyunsaturated fatty acids (PUFA) altered fatty acid composition of follicular components (Wonnacott et al, 2010) and improved membrane integrity after chilling (Zeron et al, 2002a). Fatty acid composition of follicular fluid in dairy cows is sensitive to dietary supply of polyunsaturated fatty acids (PUFA) using soybean oil (Batista et al, 2010) and flaxseed oil (Zachut et al, 2010). In vivo-produced embryos from Nellore heifers were more sensitive to cryopreservation when diets included rumen-protected PUFA Guardieiro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Feeding ewes diets high in polyunsaturated fatty acids (PUFA) altered fatty acid composition of follicular components (Wonnacott et al, 2010) and improved membrane integrity after chilling (Zeron et al, 2002a). Fatty acid composition of follicular fluid in dairy cows is sensitive to dietary supply of polyunsaturated fatty acids (PUFA) using soybean oil (Batista et al, 2010) and flaxseed oil (Zachut et al, 2010). In vivo-produced embryos from Nellore heifers were more sensitive to cryopreservation when diets included rumen-protected PUFA Guardieiro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly greater doses of CLA were fed in the mouse study by Harris et al (2001) compared with most CLA studies reported in ruminants. Additionally, a significant portion of the lipid-encapsulated supplement was likely biohydrogenated in the rumen in the study by Castañeda-Gutiérrez et al 2007a Fatty acid composition of follicular fluid is sensitive to changes in dietary supply of PUFA using soybean oil (Batista et al, 2010). Heifers fed fish oil had grater proportions of EPA and DHA in follicular fluid (Childs et al, 2008).…”
Section: Deposition Of Cla Into Animal Tissues and Productsmentioning
confidence: 97%
See 3 more Smart Citations